Draft genome sequence of Micromonospora sp. DSW705 and distribution of biosynthetic gene clusters for depsipeptides bearing 4-amino-2, 4-pentadienoate in actinomycetes. Issue 1 (December 2016) - Komaki, Hisayuki; Ichikawa, Natsuko; Hosoyama, Akira; Hamada, Moriyuki; Harunari, Enjuro; Ishikawa, Arisa; Igarashi, Yasuhiro
Abstract Here, we report the draft genome sequence ofMicromonospora sp. DSW705 (=NBRC 110037), a producer of antitumor cyclic depsipeptides rakicidins A and B, together with the features of this strain and generation, annotation, and analysis of the genome sequence. The 6.8 Mb genome ofMicromonospora sp. DSW705 encodes 6, 219 putative ORFs, of which 4, 846 are assigned with COG categories. The genome harbors at least three type I polyketide synthase (PKS) gene clusters, one nonribosomal peptide synthetase (NRPS) gene clusters, and three hybrid PKS/NRPS gene clusters. A hybrid PKS/NRPS gene cluster encoded in scaffold 2 is responsible for rakicidin synthesis. DNA database search indicated that the biosynthetic gene clusters for depsipeptides bearing 4-amino-2, 4-pentadienoate are widely present in taxonomically diverse actinomycetes.